Enhancing Organisational Transparency through Talent and Performance Management - Al-Shareef, Aisha Mustafa (2011)
Despite the negative impact of the recent global financial crisis, businesses in Dubai were fairly successful in terms of profitability. However, political and socio-economic issues related to the corporate governance were never considered a priority. In the absence of transparency, disclosure and accountability, the semi government and government organisations in Dubai can be weak in terms of trust, communication, talent retention and practicing performance management. Therefore, it is necessary to examine some ways on how we can effectively increase the practice of transparency within the semi government and government organisations. Increasing organisational transparency in Dubai semi government and government organisations is necessary in order to attract more foreign investors to invest in the country. Although Dubai and UAE is located in good strategic location, the absence of corporate governance and trust between the local government and its employees could not only weaken the relationship between the employers and employees in semi government and government sector but also the local business people and their potential foreign business partners. Two methods were used to analysis Qualitative - Focus Group and Quantitative – Online Survey. The target research respondents for this study include the UAE nationals who are currently employed in Dubai semi government and government organisations. Upon examining the perception of 135 randomly selected online research respondents, the focus of this study is to determine whether or not talent and performance management could effectively enhance organisational transparency in Dubai semi government and government organisations. For the Focus Group the target audience were 25 participants, 16 in total attended the 3 sessions scheduled. For data analysis are spondent perceptions pertaining to the significance of organisational transparency with the enhancement of talent and performance management in Dubai. The findings results suggest a strong correlation between talent management and organisational transparency, performance management and organisational transparency and setting of clear organisational objectives related to talent and 2 performance management and organisational transparency. Therefore, this study suggests a triangular link between talent management, performance management, and organisational transparency in the sense that a significant increase in organisational performance and talent management could increase employees’ trust. Because of the interrelationship between talent management, performance management and organisational transparency, this study recommends the need to provide training intervention as a way to promote transparency, the provision of comprehensive induction for new applicants, and improvements in the communication link in private organisational level. To increase transparency in government level, this study suggest the need to introduce and promote the concept of talent and performance management in local colleges and universities through government intervention, the implementation of a yearly talent management conference focused on the best corporate governance practices locally and internationally, and establish a separate government entity to conduct audit on talent management, performance management and transparency in Dubai’s semi government and government organisations. Aside from determining strategic ways in hiring, improving and retaining competitive employees, future research study should identify and design the kind of training and development programmes that will enable the semi government and government sectors in Dubai and develop a structured mechanism to link talent management to performance management, this to increase the quality of talent management, performance management and organisational transparency. It is also necessary to identify the best organisational structure to improve corporate governance, transparency in specific, in Dubai semi government and government sector.